The Influence of the Macroeconomical Variables on the Bankruptcy Rate of the Romanian Entities Working in the Agricultural Sector - Rodean (Cozma), Maria Daciana; Balteș, Nicolae (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2016)
The study’s main objective is represented by the analysis of the reasons that lead to the appearance of an agricultural companies’ default risk, based on the failure rate model developed by Wilson. In the construction of the regression model were taken into consideration the evolution of the two macroeconomic variables: the inflation rate and the variation of the exchange rate over a period of 4 years (2010-2013). The research’ results have shown that the variation of the bankruptcy rate registered by the agricultural sector is 99.99% explained by the variation of both of the macroeconomic explanatory variables.